Overview of the current promising approaches for the development of an ef- fective severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine (2020)
Coronavirus disease 2019 (COVID-19) is a pandemic infectious disease caused by the novel coronavirus called SARS-CoV-2. There is a gap in our understanding regarding the immunopathogenesis of COVID-19. However, many clinical trials are underway across the world for screening effective drugs against COVID-19. Nevertheless, currently, no proven effective therapies for this virus exists. The vaccines are deemed as a significant part of disease prevention for emerging viral diseases, since, in several cases, other therapeutic choices are limited or non‐existent, or that diseases result in such an accelerated clinical worsening that the efficacy of treatments is restricted. Therefore, effective vaccines against COVID-19 are urgently required to overcome the tremendous burden of mortality and morbidity correlated with SARS-CoV-2. In this review, we will describe the latest evidence regarding outstanding vaccine approaches and the challenges for vaccine production.